As condições de vida no nosso planeta - Lourdes , Dayane Freitas de; Carvalho , Elisângela Oliveira; Ferreira , Luciana Lopes; Carraro, Márcia Regina Simpioni; Bassan , Osvalda (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf